The human low affinity Fcgamma receptors IIa, IIb, and III bind IgG with fast kinetics and distinct thermodynamic properties. - Maenaka, K; Van Der Merwe, P; Stuart, D; Jones, E; Sondermann, P (2001)
Fcgamma receptors (FcgammaRs) are expressed on all immunologically active cells. They bind the Fc portion of IgG, thereby triggering a range of immunological functions. We have used surface plasmon resonance to analyze the kinetic and thermodynamic properties of the interactions between the ectodomains of human low affinity FcgammaRs (FcgammaRIIa, FcgammaRIIb, and FcgammaRIIIb-NA2) and IgG1 or the Fc fragment of IgG1. All three receptors bind Fc or IgG with similarly low affinities (K(D) approximately 0.6-2.5 microm) and fast kinetics, suggesting that FcgammaR-mediated recognition of aggregated IgG and IgG-coated particles or cells is mechanistically similar to cell-cell recognition. Interestingly, the Fc receptors exhibit distinct thermodynamic properties. Whereas the binding of the FcgammaRIIa and FcgammaRIIb to Fc is driven by favorable entropic and enthalpic changes, the binding of FcgammaRIII is characterized by highly unfavorable entropic changes. Although the structural bases for these differences remain to be determined, they suggest that the molecular events coupled to the binding differ among the low affinity FcgammaRs.